2020
DOI: 10.1016/j.celrep.2020.108311
|View full text |Cite
|
Sign up to set email alerts
|

Sox2 and Canonical Wnt Signaling Interact to Activate a Developmental Checkpoint Coordinating Morphogenesis with Mesoderm Fate Acquisition

Abstract: Highlights d A checkpoint stops mesoderm-fated NMPs from exiting the tailbud when expressing Sox2 d The checkpoint is activated by canonical Wnt and Sox2 interactions d The checkpoint prevents ectopic neural tissue from forming in mesodermal territories d Sox2 expression and Wnt inhibition is sufficient to induce spinal cord from NMPs

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 64 publications
(105 reference statements)
3
19
0
Order By: Relevance
“…In particular, mouse cells that have a mutation in the Brachyury gene have lower migration speed than wild-type cells when isolated and cultured, explaining part of the mouse embryonic axis truncation phenotype (34). Although a role for Sox2 in the control of progenitor cell migration has, to our knowledge, not previously been reported, recent works have demonstrated that a rise of Sox2 expression promotes the transition of posterior progenitors to NT during chick embryo secondary neurulation (35) and that turning off Sox2 is necessary for NMP to enter the mesoderm in zebrafish embryo (36). In addition, it has also been observed by time-lapse analysis that the zone between the PZ and the NT does not display excessive migration or neighbor exchanges (37).…”
Section: Discussionmentioning
confidence: 90%
“…In particular, mouse cells that have a mutation in the Brachyury gene have lower migration speed than wild-type cells when isolated and cultured, explaining part of the mouse embryonic axis truncation phenotype (34). Although a role for Sox2 in the control of progenitor cell migration has, to our knowledge, not previously been reported, recent works have demonstrated that a rise of Sox2 expression promotes the transition of posterior progenitors to NT during chick embryo secondary neurulation (35) and that turning off Sox2 is necessary for NMP to enter the mesoderm in zebrafish embryo (36). In addition, it has also been observed by time-lapse analysis that the zone between the PZ and the NT does not display excessive migration or neighbor exchanges (37).…”
Section: Discussionmentioning
confidence: 90%
“…At the 21-somite stage, the tbxta and sox2 expression domains overlapped in the TB. The expression pattern of sox2 at the 21-somite stage resembled the pattern characteristic of 12-somite stage (Kinney et al, 2020;Okuda et al, 2006;Row et al, 2016), but was more restricted and shortened further at the subsequent stages. This can be at least partly explained by the differentiation of the neural progenitors (Graham et al, 2003).…”
Section: Discussionmentioning
confidence: 66%
“…Our data on the sox2 and tbxta expression from the 21‐somite to the prim‐6 stages confirm and expand the published data. The tbxta was expressed in the notochord and throughout the TB as described previously (Bisgrove et al, 2017; Esterberg et al, 2008; Kinney et al, 2020; Morrow et al, 2017; Zhao et al, 2005). Its expression domain in the TB became smaller along with the development.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations